Mitigation Method of Rockfall Hazard on Rock Slope Using Large-Scale Field Tests and Numerical Simulations. (23rd March 2020) - Yoon, Jinam; Ban, Hoki; Hwang, Youngcheol; Park, Duhee
Abstract : This paper presents the mitigation of rockfall hazard on the large-scale rock slope using the field tests with numerical simulation. To this end, field tests including the pendulum test and real rock falling tests were performed to investigate the rock movements such as rotation, repulsion, and speed. In the simulation, the validation of the developed model followed by calibration processes was made on the field tests. In this study, a simple and new method was proposed to mitigate the rockfall hazard using the so-called sand pool made by ditching and then filling sand where the rock should be stopped or arrested. The results showed that the sand pool method was very effective and economical.